Anti‐GM2 ganglioside antibodies are a biomarker for acute canine polyradiculoneuritis. Issue 1 (22nd March 2013) - Rupp, Angie; Galban‐Horcajo, Francesc; Bianchi, Ezio; Dondi, Maurizio; Penderis, Jacques; Cappell, Joanna; Burgess, Karl; Matiasek, Kaspar; McGonigal, Rhona; Willison, Hugh J.
Abstract Acute canine polyradiculoneuritis (ACP) is considered to be the canine equivalent of the human peripheral nerve disorder Guillain‐Barré syndrome (GBS); an aetiological relationship, however, remains to be demonstrated. In GBS, anti‐glycolipid antibodies (Abs) are considered as important disease mediators. To address the possibility of common Ab biomarkers, the sera of 25 ACP dogs, 19 non‐neurological, and 15 epileptic control dogs were screened for IgG Abs to 10 glycolipids and their 1 : 1 heteromeric complexes using combinatorial glycoarrays. Anti‐GM2 ganglioside Abs were detected in 14/25 ACP dogs, and anti‐GA1 Abs in one further dog. All controls except for one were negative for anti‐glycolipid Abs. In this cohort of cases and controls, the glycoarray screen reached a diagnostic sensitivity of 60% and a specificity of 97%; a lower sensitivity (32%) was reported using a conventional glycolipid ELISA. To address the possible pathogenic role for anti‐GM2 Abs in ACP, we identified GM2 in canine sciatic nerve by both mass spectrometry and thin layer chromatography overlay. In immunohistological studies, GM2 was localized predominantly to the abaxonal Schwann cell membrane. The presence of anti‐GM2 Abs in ACP suggests that it may share a similar pathophysiology with GBS, for which it could thus be considered a naturally occurring animal model.